2012
DOI: 10.1088/1752-7155/6/1/017101
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of clinical protocols in oral malodor research

Abstract: The objective of this study is to standardize protocols for clinical research into oral malodor caused by volatile sulfur compounds (VSCs). To detect VSCs, a gas chromatograph (GC) using a flame photometric detector equipped with a bandpass filter (at 393 nm) is the gold standard (sensitivity: 5 × 10(-11) gS s(-1)). The baselines of VSC concentrations in mouth air varied considerably over a week. When the subjects refrained from eating, drinking and oral hygiene including mouth rinsing, the VSC concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 43 publications
(96 reference statements)
2
46
2
4
Order By: Relevance
“…The sample of air is collected via a 1 ml syringe, which is injected in the OralChroma ™ , after 8 minutes the concentration of the three gases is displayed in ppb or ng/10 ml (Murata et al 2006, Tangerman & Winkel 2008). Thus, Yaegaki et al (2012) reported that the detection limit for each gas was 0.54 ng/10 ml. According to the manufacturer of the OralChroma ™ device the following cut-off values for intra-oral halitosis have been proposed; H 2 S ≥ 122 ppb, MM ≥ 26 33 ppb and for DMS ≥ 8 ppb , Laleman et al 2014).…”
Section: Methods Used For the Assessment Of Intra-oral Halitosismentioning
confidence: 99%
“…The sample of air is collected via a 1 ml syringe, which is injected in the OralChroma ™ , after 8 minutes the concentration of the three gases is displayed in ppb or ng/10 ml (Murata et al 2006, Tangerman & Winkel 2008). Thus, Yaegaki et al (2012) reported that the detection limit for each gas was 0.54 ng/10 ml. According to the manufacturer of the OralChroma ™ device the following cut-off values for intra-oral halitosis have been proposed; H 2 S ≥ 122 ppb, MM ≥ 26 33 ppb and for DMS ≥ 8 ppb , Laleman et al 2014).…”
Section: Methods Used For the Assessment Of Intra-oral Halitosismentioning
confidence: 99%
“…After 4 min, the process was completed and the concentrations of three VSCs were determined by a calibration curve inside the OralChroma TM , and were displayed in either ng/mL or ppb. As spontaneous fluctuation in oral air samples has been demonstrated in several studies (Yaegaki et al, 2012;Tangerman and Winkel, 2007), three oral air samples were taken at each time point and these values were averaged.…”
Section: Measurement Of Vscs Levels By Oralchroma Tmmentioning
confidence: 99%
“…In the oral environment among other volatile sulfur compounds, H 2 S is an important compound in the development of physiological and pathological halitosis [5]. Together with periodontal disorders and dental caries, halitosis or oral malodor represents one of the main causes for which patients visit dental practices.…”
Section: Environmental Analytical Chemistrymentioning
confidence: 99%